Creación de un gimnasio en la ciudad de Quito - Moncayo Freire, Felipe Nicolás (2010)
Currently it can be noted that global trends are directed towards personal care, which has led to the emergence of a new culture based on physical care. There are many people willing to pay large sums of money for services that help them look good, improve their fitness and health. It can be seen within the city of Quito a considerable development of the service sector with 47.50% of market share, very close to the total industrial sectors with a 52.50%. About 56% of respondents attend the gym at least three times a week and 43% prefer the location in the center-north of Quito against the other three sectors. Moreover interior design draws much attention of the consumer and the extended hours had an acceptance of 66% of respondents. The company's “18 Fitness Studio” is established, a mission and a vision of the company are developed. These go along with the objectives, strategies and policies necessary for the business to function properly. For the launch and positioning of the gym and the brand, developed a marketing plan that includes strategies such as: maintaining and improving customer satisfaction and loyalty. The development of a tactical plan allows us to show: the service, distribution, promotion and advertising. The financial analysis determined the feasibility in the six scenarios projected to five years, the optimistic scenario is the most favorable leveraged with an IRR of 68% and a NPV of $ 89,961.84. Accordingly to the business plan developed, the opportunity is favorable to be implemented.